Factors affecting the strength of denture repairs: Topics of interest - Seó, Rosangela Seiko [UNESP]; Neppelenbroek, Karin Hermana [UNESP]; Filho, João Neudenir Ariolli [UNESP] (Wiley, 2007)
Fracture of dentures is a common clinical finding in daily prosthodontic practice, resulting in great inconvenience to both patient and dentist. A satisfactory repair should be cost-effective, simple to perform, and quick; it should also match the original color and not cause distortion to the existing denture. Different repair materials, surface designs, and mechanical and chemical surface treatments have been recommended in order to obtain stronger repairs. This article reviews some of the available literature with regard to the most important factors that may influence the strength of denture repairs. © 2007 by The American College of Prosthodontists.
Keywords: Acrylic resin; Surface; Treatment; biomedical and dental materials; chemistry; cost benefit analysis; dental care; economics; human; methodology; standard; surface property; time; tooth prosthesis; Cost-Benefit Analysis; Dental Materials; Dental Prosthesis Repair; Esthetics, Dental; Humans; Surface Properties; Time Factors